Hydrogenated Anatase: Strong Photocatalytic Dihydrogen Evolution without the Use of a Co‐Catalyst1. Issue 51 (19th October 2014) - Liu, Ning; Schneider, Christopher; Freitag, Detlef; Venkatesan, Umamaheswari; Marthala, V. R. Reddy; Hartmann, Martin; Winter, Benjamin; Spiecker, Erdmann; Osvet, Andres; Zolnhofer, Eva M.; Meyer, Karsten; Nakajima, Tomohiko; et al.
Abstract The high‐pressure hydrogenation of commercially available anatase or anatase/rutile TiO2 powder can create a photocatalyst for H2 evolution that is highly effective and stable without the need for any additional co‐catalyst. This activation effect cannot be observed for rutile; however, for anatase/rutile mixtures, a strong synergistic effect can be found (similar to results commonly observed for noble‐metal‐decorated TiO2). EPR and PL measurements indicated the intrinsic co‐catalytic activation of anatase TiO2 to be due to specific defect centers formed during hydrogenation. These active centers can be observed specifically for high‐pressure hydrogenation; other common reduction treatments do not result in this effect.